Comportamento mecânico de cerâmicas parcialmente cristalinas submetidas à fadiga cíclica - Vicari, Carolina Barbosa (2015)
Objective: To evaluate the mechanical behavior of two partially crystalline ceramics, a leucite-based glass-ceramic (IPS Empress® CAD), VL, and a lithium disilicate-based glass-ceramic (IPS e-max® CAD), VD, subjected to a cyclic fatigue test. Material and Methods: Seventy bar-shaped specimens were produced for each ceramic, with dimensions of 16 mm x 4 mm x 1.2 mm, by cutting pre-fabricated CAD-CAM blocks. For each group, thirty specimens were subjected to a three-point bending test in a universal testing machine and 40 specimens were subjected to cyclic fatigue test. The cyclic fatigue test was performed using the boundary technique with 1 Hz frequency, in 37 ° C distilled water using a pneumatic cycling machine. Fractographic analysis of the fractured specimens was performed with a scanning electron microscope (SEM). Data were statistically analyzed using the Weibull analysis and Mann-Whitney test (α = 0.05). Results: VD group (244 MPa) showed statistically superior flexural strength values than VL group (122 MPa). However, VL group obtained higher Weibull modulus. Both groups showed a reduction of, approximately, 60% of the initial flexural strength after cycling for 104 cycles. For VD group tested in fatigue, there was no degradation of the flexural strength values when the number of cycles was increased (104 to 105). VL group showed a decrease in strength of 17% when the number of cycles was increased from 103 to 104. Flexural strength values estimated for a probability of failure of 5% were 36 MPa, for VL group, and 58 MPa, for VD group, after the same number of cycles (104 cycles). Conclusion: Lithium disilicate-based glass-ceramic has superior mechanical and fatigue behavior than leucite-based glass-ceramic, besides its lower reliability. In addition, it can be concluded that mechanical cycling in humid conditions proved to be an important factor for the degradation of the mechanical properties of ceramics.